ANALISIS PENERAPAN STANDAR PROSES DI SD ISLAM NURUS SUNNAH - Nuansa Ayu Prisca Andini; Anita Nadzifah; Ratih Setianingrum; Rina Ardani; Soedjono, Soedjono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Education in Indonesia has 8 national education standards which are listed in PP No. 4 of 2022 concerning National Education Standards (SNP) article 3. These 8 standards are used to guarantee the quality of education. One standard that can guarantee quality in terms of the learning process is the process standard. The process standard includes: lesson planning, lesson implementation, and assessment of the learning process. Currently, the implementation of the new independent curriculum has been implemented and it has been found that some teachers at Nurus Sunnah Islamic Elementary School still have difficulty in planning learning, carrying out the learning process, and assessing according to the independent curriculum. Based on these findings, the researchers were motivated to analyze the implementation of the education process standards at Nurus Sunnah Islamic Elementary School. The method used in this research is descriptive qualitative with data collection techniques through interviews, observations, and documentation. The instruments used in data collection are interview guides, observation sheets, and documentation. The results of the study show that the obstacles for teachers in making lesson plans are because teachers are still unable to make lesson plan documents, analyze learning achievements so that they produce TP and ATP. The learning process has been carried out in an interactive, inspiring, enjoyable, challenging, and motivating way so that students can actively participate. In assessment activities, teachers still do not understand formative and summative assessment.